Pelatihan partnership guru dan orang tua dalam mengembangkan model contextual teaching and learning dengan media loose parts untuk menstimulasi kreativitas anak usia dini - Leli Halimah; Margaretha Sri Yuliartiningsih; Nenden Ineu Herwati; Mirawati Mirawati; Ayu Hopiani (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2021)
Various theories and research results reveal that an effective partnership between school and family are a necessity, the key to success, and  a critical factor in the academic and socio-emotional development of children. Judging from the urgency of the school-family partnership in helping the success of children's education, it is very necessary to have a comprehensive understanding on the part of both teachers and parents in its implementation. For this reason, through this community service activity, it aims to provide insight and skills, especially to early childhood teachers who are partners in the implementation of PPLSP PGPAUD UPI Campus Cibiru. The results of the activity show an increase in partnership literacy between teachers and parents regarding the nature of the importance of partnerships, types, principles, strategies and approaches to partnerships. In addition, teachers have the skills to plan partnership programs, and have a positive attitude to be even better in creating partnerships with children's parents in developing contextual teaching and learning models with loose parts media to stimulate early childhood creativity.